2012
DOI: 10.1039/c2cc32147e
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic, enantio- and diastereoselective synthesis of γ-butyrolactones incorporating quaternary stereocentres

Abstract: A new, highly enantio- and diastereoselective catalytic asymmetric formal cycloaddition of aryl succinic anhydrides and aldehydes which generates paraconic acid (γ-butyrolactone) derivatives is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Gratifyingly, the scope of the methodology is not confined to homophthalic anhydride derivatives: the phenyl glutaconic anhydride (28), and its methyl variant 29, underwent smooth cycloaddition to afford the highly substituted cyclohexenones 34 and 35, respectively in excellent yields and with near optical purity (entries 5 and 6). These reactions represent the first examples of the expansion of enantioselective cycloadditions involving enolizable anhydrides beyond either homophthalic- [10] or a-aryl succinic [11] analogues. To demonstrate the potential of this protocol for the rapid, efficient, and enantioselective synthesis of complex products, the tricyclic anhydride 30 was reacted with 17 under the influence of 24 to generate 36 in high yield and 99 % ee (entry 7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gratifyingly, the scope of the methodology is not confined to homophthalic anhydride derivatives: the phenyl glutaconic anhydride (28), and its methyl variant 29, underwent smooth cycloaddition to afford the highly substituted cyclohexenones 34 and 35, respectively in excellent yields and with near optical purity (entries 5 and 6). These reactions represent the first examples of the expansion of enantioselective cycloadditions involving enolizable anhydrides beyond either homophthalic- [10] or a-aryl succinic [11] analogues. To demonstrate the potential of this protocol for the rapid, efficient, and enantioselective synthesis of complex products, the tricyclic anhydride 30 was reacted with 17 under the influence of 24 to generate 36 in high yield and 99 % ee (entry 7).…”
Section: Methodsmentioning
confidence: 99%
“…The Michael acceptor 17 was reacted with a range of enolizable anhydrides 1 and 25-30 in the presence of 24 at 30 8C ( Table 2). These reactions represent the first examples of the expansion of enantioselective cycloadditions involving enolizable anhydrides beyond either homophthalic- [10] or a-aryl succinic [11] analogues. The brominated analogue 31 was formed with comparable efficacy and stereocontrol (entry 2).…”
mentioning
confidence: 99%
“…We have recently10 shown that the bifunctional organocatalyst 9 can promote the formal cycloaddition of benzaldehyde ( 8 ) to 1 to afford the substituted dihydroisocoumarin lactone 10 with excellent yield, and enantio‐ and diastereocontrol (Figure 1 D). 11 We had posited that 9 both catalyzes the tautomeric equilibrium between 1 and 2 c and organizes the encounter between 2 c and the squaramide‐bound 8 by general acid‐base catalysis. This offers the possibility of an extension to conjugated electrophiles, and the first enantioselective Tamura cycloaddition reactions.…”
Section: Catalyst Evaluation and Optimizationmentioning
confidence: 99%
“…Gratifyingly, the scope of the methodology is not confined to homophthalic anhydride derivatives: the phenyl glutaconic anhydride ( 28 ), and its methyl variant 29 , underwent smooth cycloaddition to afford the highly substituted cyclohexenones 34 and 35 , respectively in excellent yields and with near optical purity (entries 5 and 6). These reactions represent the first examples of the expansion of enantioselective cycloadditions involving enolizable anhydrides beyond either homophthalic‐10 or α‐aryl succinic11 analogues. To demonstrate the potential of this protocol for the rapid, efficient, and enantioselective synthesis of complex products, the tricyclic anhydride 30 was reacted with 17 under the influence of 24 to generate 36 in high yield and 99 % ee (entry 7).…”
Section: Catalyst Evaluation and Optimizationmentioning
confidence: 99%
“…Although there are only a few examples where anhydride enols have been reported as reactive intermediates, 10 they have been studied computationally, 11 observed crystallographically, 12 and suggested as key intermediates in a related lactone-forming reaction. 13 A proton transfer leads to the reactive iminium 20 and enolate 21 intermediates. The Mannich step occurs with high diastereoselectivity through the pseudo-Zimmerman-Traxler transition state 22 with intermolecular hydrogen bonding complexation.…”
mentioning
confidence: 99%